PENERAPAN MODEL PEMBELAJARAN BERMAIN DAN MUSIK UNTUK MENINGKATKAN HASIL BELAJAR PAI PESERTA DIDIK SMP BP AL MUNAWWAROH MERAUKE - SRI WAHYUNINGSIH (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2023)
This study aims to improve the learning outcomes of the PAI Budi Pekerti subject on commendable morals for class IIA SMP Al Munawwaroh Merauke Islamic Boarding School in the 2022/2023 academic year, by applying the learning model "Model of Playing and Music." The type of research used was Classroom Action Research (CAR) which was carried out in two cycles to see the learning process and the improvement of student learning outcomes in participating in learning commendable morals material through the learning model approach "Model of Play and Music." The subjects of this study were students of class IIA SMP Al Munawwaroh Merauke Islamic Boarding School, totaling 19 children. Data collection techniques in PTK consist of tests and observations. The data collected in each test activity and observation from the implementation of each PTK cycle were analyzed descriptively using the percentage technique to see the learning process and the improvement of learning outcomes. The results of the study can be concluded with the learning model "Model of Play and Music" the learning process becomes more optimal and learning outcomes increase. From the initial conditions, the acquisition of the PAI Budi Pekerti subject matter on commendable morals was 26.315%, at the end of cycle 1 it increased to 68.421%, and at the end of cycle 2 the learning outcomes increased to 89.473%. Based on the results of the study, it was concluded that the application of the learning model "Play and Music," can improve learning outcomes in the Islamic Religious Education (PAI) Subject of Good Morals in class VIIIA SMP Based Al Munawwaroh Merauke Islamic Boarding School for the 2022/2023 academic year. ABSTRAKPenelitian ini bertujuan untuk peningkatan hasil belajar mapel PAI Budi Pekerti materi akhlaq terpuji kelas VIIIA SMP Berbasis Pesantren Al Munawwaroh Merauke pada tahun pelajaran 2022/2023, dengan penerapan model pembelajaran “Model Bermain dan Musik.” Jenis penelitian yang dipakai adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan pada dua siklus untuk melihat proses belajar dan peningkatan hasil belajar peserta didik dalam mengikuti pembelajaran materi akhlaq terpuji melalui pendekatan model pembelajaran “Model Bermain dan Musik.” Subyek penelitian ini adalah peserta didik kelas VIIIA SMP Berbasis Pesantren Al Munawwaroh Merauke, berjumlah 19 anak. Tehnik pengumpulan data dalam PTK ini terdiri dari tes dan observasi. Data yang dikumpulkan pada setiap kegiatan tes dan observasi dari pelaksanaan setiap siklus PTK dianalisis secara deskriptif dengan menggunakan tehnik presentase untuk melihat proses belajar dan peningkatan hasil belajar. Hasil penelitian dapat disimpulkan dengan model pembelajaran “Model Bermain dan Musik” proses pembelajaran menjadi lebih optimal dan hasil belajar meningkat. Dari kondisi awal perolehan nilai mapel PAI Budi Pekerti pada materi akhlaq terpuji 26, 315%, pada pada akhir siklus 1 meningkat menjadi 68,421%, dan pada akhir siklus 2 hasil belajar meningkat menjadi 89, 473%. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa penerapan model pembelajaran model “Bermain dan Musik,” dapat meningkatkan hasil belajar mata pelajaran Pendidikan Agama Islam (PAI) Budi Pekerti materi akhlaq terpuji kelas VIIIA SMP Berbasis Pesantren Al Munawwaroh Merauke tahun pelajaran 2022/2023.